Driving Green Open Access - Hole, Brian (Septentrio Conference Series, 2020)
See RECORDING (starts at 01:35:17). Ubiquity Press was founded to catalyze and accelerate the adoption of open access. Until now we have followed the gold and diamond models, and currently support OA publication in over 700 journals, plus hundreds of book publications per year. We are now expanding our platform to fully support and drive the uptake and effectiveness of green open access also. In this presentation I will explain how we are doing this by integrating an open source repository solution with our platform. I will detail the features being added to especially enhance green OA, as part of the Advancing Hyku project with funding from Arcadia, a charitable fund of philanthropists Lisbet Rausing and Peter Baldwin, and in partnership with the University of Virginia and the British Library.